"Friendship Brought Me Into it, but Commitment Bought Me Into it": Civic Engagement Motivations Among Highly Engaged Asian American Youth. Issue 11 (November 2021) - Cheung, Amy
Background/Context: There is currently a dearth of research on Asian American civic engagement broadly, and the scholarship on Asian American youth is even more limited. The lack of research contributes to opacity in understanding how Asian Americans fit into the civic landscape. Purpose/Objective/Research Question/Focus of Study: This study offers a window into the civic engagement experiences of a group of Asian American youth and differentiates the motivations that initiated their civic engagement from the motivations that sustained it. The research questions are: (a) How do these Asian American adolescents describe the motivations behind their civic engagement? (b) How do they make choices among different kinds of civic engagement? (c) What do they describe as the impact of their civic engagement? Research Design: Participants in this study were 14 highly engaged Asian American youth, 16 to 18 years of age, from a small city in the Northeast. I conducted semistructured interviews with the participants, examining their descriptions of civic involvement. Knowledge of youth civic engagement has tended to emanate from survey studies that count and categorize civic participation as opposed to investigating youth's own meaning-making of their civic activities. Thus, to answer the "why" of civic participation, I took a grounded theory approach to explore youth's own constructions of what motivated their civic involvement. Findings/Results: Participants initiated civic involvement with instrumental motivations to "look good for college" and socialize with friends, whereas continuing civic engagement was supported by a deep relational commitment to teenage colleagues in their civic endeavors, a sense of self-efficacy engendered through complex civic work, and pride in making a tangible impact on their community. Asian American youth in this study demonstrated sophisticated capabilities as civic actors and sustained their civic engagement through organizations that scaffolded the development of such capabilities. Conclusions/Recommendations: Participants' experiences illustrate how civic engagement motivations can change. While individuals were the unit of analysis in this study, participants' experiences point strongly to the integral role of organizations in supporting continued, rather than intermittent, civic engagement. Specifically, organizations can support youth in continuing their civic involvement in the long term by facilitating conditions for young people to build deep relationships in furtherance of common goals and appealing to identities that can be bolstered through civic participation.